SISTEM INFORMASI BURSA KERJA KHUSUS DENGAN REKOMENDASI MENGGUNAKAN METODE CONTENT BASED FILTERING DI STMIK YADIKA BANGIL - M. Noval Riswandha; Miftakhul Nuryuda (Joutica, 2018)
The author makes a special job stock information system (BKK) in STMIK YADIKA Bangil because the job search process for alumni students is currently running less effectively, alumni students should seek information to BKK officers, while BKK officers have to look for alumni data who have not got a job. Therefore, the authors make a special job market information system with recommendations using content based filtering method. Content based filtering method can be used to suggest job vacancy information in accordance with user profile or job seeker so as to facilitate the information search process.System of recommendation in the application of special job market is used to recommend the right job vacancy information for the alumni of the student.In this system expected alumni students Can receive job vacancy information properly and in accordance with the criteria it has